Antioxidant copper conductive particles, a preparation method thereof and a conductive adhesive
Patent Information
- Application Number
- CN202610799673.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]为了解决上述技术问题,本发明提出一种抗氧化铜导电粒子及其制备方法、导电胶,旨在解决现有技术中核壳结构导电粒子制备工艺复杂、使用有毒试剂、铜壳层易氧化失效的问题
[0017]有益效果,与现有技术相比,本发明通过利用导电高分子与银盐的联用替代了传统化学镀铜的粗化、敏化、活化三步预处理。步骤简化,省去高污染试剂,缩短制备周期。无需使用浓硫酸、重铬酸钾、氯化钯、甲醛,环保性好。银盐活化液可重复利用,成本进一步降低。核壳结构减少了金属材料用量,降低成本。甲酸盐水热与硫醇处理形成的抗氧化保护层使铜导电粒子在导通电阻变化率仅4.17%以内(现有未处理铜导电粒子变成绝缘粒子),同时保持高导电性。
Smart Images

Figure CN122907412A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic material packaging technology, and in particular to an antioxidant copper conductive particle, its preparation method, and a conductive adhesive. Background Technology
[0002] With the rapid development of microelectronics technology towards high density, miniaturization, and flexibility, conductive adhesives, as environmentally friendly alternatives to traditional tin-lead solders, are widely used in chip packaging, printed circuit board interconnection, and flexible electronic device assembly due to their advantages such as low curing temperature, simple process, strong compatibility, and lead-free and pollution-free properties. The core performance of isotropic conductive adhesives is determined by the conductivity, dispersibility, stability, and compatibility with the matrix of the conductive filler.
[0003] Existing conductive fillers have the following problems in practical applications. Pure silver particles have excellent conductivity, but silver resources are scarce and expensive. Nanoscale silver particles have a large specific surface area and high surface activity, making them prone to aggregation, resulting in uneven formation of the conductive network in the conductive adhesive and affecting connection reliability. Pure copper particles are much cheaper than silver and have good conductivity, but they are chemically reactive and easily oxidized in air to form an insulating copper oxide film, leading to a sharp decrease in conductivity or even loss of conductivity. Carbon-based particles have far lower conductivity than metal particles, making it difficult to meet low resistance requirements.
[0004] To address the aforementioned issues with conductive fillers, a core-shell structured conductive filler has been proposed, combining the superior properties of both the core and shell layers to achieve a balance between performance and cost. However, existing core-shell structured conductive particle preparation methods suffer from the following problems: Traditional chemical copper plating methods require three pretreatment steps: roughening, sensitization, and activation. The roughening step uses concentrated sulfuric acid or potassium dichromate to etch the microsphere surface to increase roughness. The sensitization step uses high-concentration hydrochloric acid and stannous chloride to adsorb tin ions onto the microsphere surface. The activation step uses high-concentration hydrochloric acid and palladium chloride to replace the tin ions with palladium catalytic cores. These steps are cumbersome, utilize large amounts of high-concentration strong acids and the precious metal palladium, and pose environmental and health risks.
[0005] Therefore, the existing technology still needs further development and improvement. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention proposes an antioxidant copper conductive particle, its preparation method, and a conductive adhesive, aiming to solve the problems of complex preparation processes, use of toxic reagents, and easy oxidation and failure of the copper shell layer in existing core-shell structure conductive particles. Specifically: In a first aspect, a method for preparing antioxidant copper conductive particles includes the following steps: By modifying the surface of polymer microspheres with conductive polymer materials, polymer composite microspheres are obtained. The polymer composite microspheres were treated with silver ammonia solution to obtain activated microspheres; The activated microspheres were added to a copper plating solution containing copper salt, complexing agent and reducing agent for chemical copper plating to obtain copper conductive particles; The copper conductive particles are subjected to formate hydrothermal treatment and thiol treatment in sequence to form an antioxidant layer on the surface of the copper conductive particles, thereby obtaining the antioxidant copper conductive particles.
[0007] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The purpose and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.
[0008] As a preferred technical solution, in the preparation method, the conductive polymer material is polyaniline and / or polydopamine.
[0009] As a preferred technical solution, in the preparation method, the polymer microspheres are made of one or a copolymer of polystyrene, polymethyl methacrylate, polyurethane, phenolic resin, polydimethoxysiloxane, and silica. Preferably, the particle size of the polymer microspheres is 500 nm to 200 μm.
[0010] As a preferred technical solution, in the preparation method, the silver ammonia solution is prepared by silver salt and ammonia water, wherein the silver salt is silver sulfate or silver nitrate.
[0011] As a preferred technical solution, in the preparation method, the copper salt is one or more of copper sulfate, copper chloride, and copper nitrate; the complexing agent is disodium ethylenediaminetetraacetate; and the reducing agent is one or more of dimethylamineborane (DMAB), sodium hypophosphite, and sodium borohydride.
[0012] As a preferred technical solution, in the preparation method, the temperature of the chemical copper plating is 30~70℃ and the pH is 7~9.
[0013] As a preferred technical solution, in the preparation method, the formate is sodium formate or ammonium formate; and the thiol is dodecyl mercaptan.
[0014] Secondly, an antioxidant copper conductive particle prepared by the above-described preparation method, comprising: Polymer microspheres; A conductive polymer intermediate layer coating the surface of the polymer microspheres; A copper metal layer covering the surface of the conductive polymer intermediate layer; and an anti-oxidation layer formed on the surface of the copper metal layer.
[0015] Thirdly, a conductive adhesive comprising the antioxidant copper conductive particles, resin, and curing agent described in the second aspect.
[0016] As a preferred technical solution, the conductive adhesive, wherein the resin includes: thermosetting resin and / or thermoplastic resin, and the curing agent includes: one or more of imidazole curing agents, acid anhydride curing agents, and amine curing agents.
[0017] Beneficial effects: Compared with existing technologies, this invention replaces the three-step pretreatment of roughening, sensitization, and activation in traditional chemical copper plating by using a combination of conductive polymers and silver salts. The process is simplified, eliminating highly polluting reagents and shortening the preparation cycle. It eliminates the need for concentrated sulfuric acid, potassium dichromate, palladium chloride, and formaldehyde, making it environmentally friendly. The silver salt activation solution can be reused, further reducing costs. The core-shell structure reduces the amount of metal material used, lowering costs. The antioxidant protective layer formed by hydrothermal treatment of formate and thiol ensures that the copper conductive particles maintain a conductivity change rate of less than 4.17% (unlike untreated copper conductive particles which become insulating particles), while retaining high conductivity. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the drawings used in the description of the embodiments or related technologies will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a schematic diagram illustrating the principle of the palladium-free electroless copper plating process in this invention.
[0020] Figure 2 This is a schematic diagram of the antioxidant treatment process in this invention.
[0021] Figure 3 This is a thermogravimetric analysis curve of the microspheres in an embodiment of the present invention.
[0022] Figure 4 The images shown are scanning electron microscope (SEM) images of PS@PANI&Ag@Cu conductive particles from various embodiments of the present invention, wherein a is prepared in Example 1, b is prepared in Example 2, c is prepared in Example 3, d is prepared in Example 4, e is prepared in Example 5, f is prepared in Example 6, and g is prepared in Example 7.
[0023] Figure 5The images shown are scanning electron microscope (SEM) images of PS@PANI & Ag@Cu conductive particles from various comparative examples of this invention. Specifically, a represents particles prepared in Comparative Example 1, b represents particles prepared in Comparative Example 2, c represents particles prepared in Comparative Example 3, d represents particles prepared in Comparative Example 4, and e represents particles prepared in Comparative Example 5.
[0024] Figure 6 These are scanning electron microscope (SEM) images comparing the effects of PANI and silver salts in the comparative examples of this invention. In the images, a represents the particles prepared in Comparative Example 6, b represents the particles prepared in Comparative Example 7, and c represents the particles prepared in Comparative Example 8.
[0025] Figure 7 This is a schematic diagram of the sample preparation process for conductive adhesive resistance testing in this invention. Detailed Implementation
[0026] The embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and should not be construed as limiting the scope of the invention.
[0027] In the description of the embodiments of the present invention, it should be noted that the terms "center," "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of the present invention. In addition, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0028] In the description of the embodiments of the present invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "connected" and "linked" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium. Those skilled in the art can understand the specific meaning of the above terms in the embodiments of the present invention based on the specific circumstances.
[0029] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0030] like Figure 1 As shown, this invention provides a method for preparing antioxidant copper conductive particles, comprising: using composite microspheres (PS@PANI) with a surface modified with conductive polymer material as raw material, and pretreating (roughening) their surface; then activating the pretreated PS@PANI with Ag, i.e., contacting PS@PANI with silver ammonia solution, followed by centrifugation to obtain activated microspheres (PS@PANI&Ag); then adding the activated microspheres to a copper plating solution containing copper salt, complexing agent, and reducing agent, and adjusting the pH of the copper plating solution to alkaline, to obtain PS@PANI&Ag@Cu conductive particles. Figure 2 As shown, to enhance the oxidation resistance of the PS@PANI&Ag@Cu conductive particles, an anti-oxidation treatment is performed. This involves sequentially subjecting the copper conductive particles to formate hydrothermal treatment and thiol treatment, forming an anti-oxidation layer on the surface of the copper metal layer, resulting in anti-oxidation copper conductive particles (PS@PANI&Ag@Cu-FA / DT). 1. By combining conductive polymers (polyaniline, PANI) with silver salts, the traditional three steps of roughening, sensitization, and activation in electroless copper plating are eliminated, avoiding the use of highly polluting reagents (concentrated sulfuric acid, potassium dichromate, high-concentration hydrochloric acid, palladium chloride, formaldehyde), reducing environmental and health risks, while shortening the preparation cycle and improving production efficiency. The use of a silver salt activation solution of silver sulfate and ammonia to replace the traditional palladium chloride activation mechanism completely eliminates dependence on the precious metal palladium, achieving low-cost, environmentally friendly, more stable processes, and superior plating performance in electroless / electroplating activation.
[0031] In one implementation of this embodiment, the conductive polymer material includes, but is not limited to, polyaniline and / or polydopamine. Polyaniline (PANI) can adsorb silver ions, and the reduced silver particles can serve as reduction sites, providing a basis for subsequent copper plating.
[0032] In one implementation of this embodiment, the polymer microspheres are made of materials including, but not limited to, polystyrene, polymethyl methacrylate, polyurethane, phenolic resin, and polydimethoxysiloxane; the particle size of the polymer microspheres is 500 nm to 200 μm. The particle size of the polymer microspheres can be 500 nm to 700 nm, 700 nm to 900 nm, 900 nm to 1000 nm, 1 μm to 10 μm, 10 μm to 20 μm, 20 μm to 30 μm, 30 μm to 40 μm, 40 μm to 50 μm, 50 μm to 60 μm, 60 μm to 70 μm, 70 μm to 80 μm, or 80 μm to 90 μm. μm, 90μm to 100μm, 100μm to 110μm, 110μm to 120μm, 120μm to 130μm, 130μm to 140μm, 140μm to 150μm, 150μm to 160μm, 160μm to 170μm, 170μm to 180μm, 180μm to 190μm, 190μm to 200μm.
[0033] In one implementation of this embodiment, the copper salt is one or more of copper sulfate, copper chloride, and copper nitrate; the complexing agent is disodium ethylenediaminetetraacetate; and the reducing agent is one or more of dimethylamineborane, sodium hypophosphite, and sodium borohydride. The combined use of the reducing agent with the aforementioned two-step process of polyaniline and silver salt solution achieves palladium-free electroless copper plating.
[0034] In one implementation of this embodiment, the temperature of the electroless copper plating is 30~70℃, such as the heating temperature is 30℃ to 40℃, 40℃ to 50℃, 50℃ to 60℃, or 60℃ to 70℃; and the pH is 7~9.
[0035] Based on the same inventive concept, this invention also provides an antioxidant copper conductive particle, comprising: a polymer microsphere core; a conductive polymer intermediate layer coating the surface of the polymer microsphere core; a copper metal layer coating the surface of the conductive polymer intermediate layer; and an antioxidant layer formed on the surface of the copper metal layer. It is readily understood that the interior of this antioxidant copper conductive particle is a polymer microsphere, with a conductive polymer intermediate layer modified on the surface of the polymer microsphere, a copper metal layer coating the surface of the conductive polymer intermediate layer, and an antioxidant layer formed on the surface of the copper metal layer. Due to the presence of the antioxidant layer, the conductive particle can maintain high conductivity in environments with high relative humidity. Using copper as the conductive metal layer replaces traditional expensive gold and silver, simplifies the preparation process, reduces raw material and production costs, and is suitable for mass production line operations, possessing potential for industrial application. Thermogravimetric analysis of the microspheres is as follows: Figure 3As shown. Thermogravimetric analysis of the microspheres showed that the mass fractions of the PS core, PANI layer, silver activation layer and copper layer were 64.46 wt.%, 8.52 wt.%, 7.13 wt.% and 19.89 wt.%, respectively.
[0036] Based on the same inventive concept, embodiments of the present invention also provide a conductive adhesive comprising the aforementioned antioxidant copper conductive particles, resin, and curing agent. The resin is primarily a thermosetting resin or a thermoplastic resin. Thermosetting resins mainly include, but are not limited to, epoxy resins, acrylic resins, and multifunctional polyurethanes, while thermoplastic resins mainly include, but are not limited to, polyurethanes, polyacrylates, polyvinyl alcohol, and polyvinyl butyral. These resins ensure the stability of the joints during bonding with the anisotropic conductive adhesive.
[0037] For curing agents, epoxy resins primarily use imidazole, acid anhydride, and amine curing agents, including but not limited to imidazole, dimethylimidazolium, diphenylimidazolium, dicyandiamide, phthalic anhydride, and tetrahydrophthalic anhydride. For acrylic / methacrylic acid resins, curing initiators mainly include azobisisobutyric acid and benzoyl peroxide. The use of curing agents can initiate the cross-linking reaction of thermosetting resins during the bonding process, thus achieving the function of bonding components. Additionally, conductive fillers serve to conduct electrical circuits during the bonding process.
[0038] The following specific preparation examples will further explain and illustrate the above-mentioned technical solutions provided by the present invention.
[0039] Example 1 Polystyrene microspheres with an average particle size of approximately 10 μm were selected as the polymer microspheres. The polystyrene microspheres were dispersed in a 0.1 M hydrochloric acid aqueous solution containing aniline monomers, and excess ammonium persulfate was added as an oxidation initiator. The reaction was carried out under stirring in an ice bath at 0–5 °C for 6 h. The aniline monomers underwent in-situ oxidative polymerization on the surface of the microspheres, forming a polyaniline (PANI) coating layer. The PANI molecular chains uniformly coated the surface of the microspheres, forming a continuous conductive polymer modification layer, resulting in PS@PANI composite microspheres.
[0040] Weigh 1g of silver sulfate and add it to 100ml of deionized water, stirring to dissolve. Add approximately 2.5ml of 28% ammonia solution dropwise, observing the color change: initially turning brownish-yellow (indicating the formation of silver oxide colloid), then becoming colorless and transparent after further ammonia addition (indicating the formation of soluble silver ammonia complex ions). Add PS@PANI composite microspheres to the silver ammonia solution and stir at room temperature for 1 hour. The amino and imino functional groups on the PANI molecular chain have the ability to complex and adsorb silver ammonia complex ions, enriching silver ions on the PANI surface. After adsorption, the reducing conjugated structure in the PANI molecular chain reduces the adsorbed silver ions in situ to silver nanoparticles, obtaining activated microspheres. Centrifuge and wash three times with deionized water. The silver ammonia activation solution can be recovered and reused multiple times after adding a small amount of silver salt.
[0041] Activated microspheres were added to a reaction vessel, followed by 100 ml of deionized water, 2 g of copper sulfate, and 10.4 g of disodium ethylenediaminetetraacetate. The mixture was magnetically stirred to disperse the microspheres, and the pH was adjusted to 9 with ammonia. The solution was heated to 50°C, and 0.5 g of dimethylamine borane was added. Under alkaline conditions, dimethylamine borane hydrolyzed, releasing borane and hydrogen gas. The borane reduced copper ions to metallic copper, forming a dense copper shell. After 1 hour of reaction, the surface of the microspheres was completely covered by the copper shell, yielding PS@PANI&Ag@Cu conductive particles. The particles were then centrifuged and washed three times with deionized water.
[0042] PS@PANI&Ag@Cu conductive particles were added to a solution containing 0.5g sodium formate and 100ml deionized water and ultrasonically dispersed for 2min. The mixture was then transferred to a polytetrafluoroethylene-lined high-pressure reactor, sealed, and heated to 200℃ for 24h. Under high-temperature and high-pressure hydrothermal conditions, formate ions reacted with copper oxide on the copper shell surface, reducing the surface copper oxide to metallic copper and simultaneously forming a dense copper formate complex protective film. After hydrothermal treatment, the mixture was allowed to cool naturally, washed three times with deionized water by centrifugation, and vacuum dried. The dried conductive particles were then added to a solution containing 0.1g dodecyl mercaptan and 50ml ethanol and stirred for 5min. The thiol (SH) groups of dodecyl mercaptan strongly chemisorbed onto copper atoms on the copper surface, forming a tightly packed monolayer self-assembled film. The thiol molecules in the monolayer were arranged with the alkyl chains facing outwards, forming a hydrophobic barrier on the copper surface, effectively blocking contact between oxygen and moisture. After washing with ethanol, centrifuging three times, and drying, the PS@PANI&Ag@Cu conductive particles were obtained. Its scanning electron microscope image is as follows Figure 4 As shown in 'a', the results indicate that the condition is good.
[0043] Example 2 The amount of copper sulfate used was 4g, and the rest was the same as in Example 1. With the increase in copper ion concentration in the copper plating solution, the deposition rate increased, and the copper layer on the microsphere surface became uniform and dense. Its scanning electron microscope image is shown below. Figure 4 As shown in b, the results indicate that the condition is good.
[0044] Example 3 The amount of disodium ethylenediaminetetraacetate (EDTA) used was 5.2 g, and the rest was the same as in Example 1. The amount of complexing agent was reduced but sufficient to stabilize the copper ions, resulting in good copper plating performance. The scanning electron microscope image is shown below. Figure 4 As shown in c in the figure.
[0045] Example 4 The copper plating temperature was 70°C, and the rest was the same as in Example 1. The increased temperature accelerated the reaction rate, resulting in more complete copper layer deposition. The scanning electron microscope image is shown below. Figure 4 As shown in d.
[0046] Example 5 The copper plating pH was 7, and the rest was the same as in Example 1. Even with the pH lowered, the catalytic activity of the silver seed layer was still sufficient to initiate copper deposition, resulting in good copper plating performance. The scanning electron microscope image is shown below. Figure 4 As shown in e.
[0047] Example 6 The amount of dimethylamine borane used was 1g, and the rest was the same as in Example 1. Increased reducing agent concentration enhanced the driving force of the reduction reaction, resulting in more complete copper deposition. The scanning electron microscope image is shown below. Figure 4 As shown in f in the figure.
[0048] Example 7 The amount of copper sulfate used was 1g, and the rest was the same as in Example 1. The decrease in copper salt concentration led to a lower deposition rate, but the copper layer remained uniform. Its scanning electron microscope image is shown below. Figure 4 As shown in g in the figure.
[0049] Example 8 Take 4g of PS@PANI&Ag@Cu conductive particles from Example 1, add 3.6g of bisphenol A type epoxy resin and 0.4g of dimethylimidazole curing agent, vacuum stir in a planetary mixer for 15 minutes, degas, and then coat onto a clean glass substrate. Figure 7 As shown, it was cured on a hot plate at 150℃ for 30 min. The volume resistivity was measured to be 7.2 × 10⁻⁶ using the four-probe method. -3 The resistivity of the sample after aging in an 85℃, 85%RH constant temperature and humidity chamber for 200 hours was measured to be 7.5 × 10⁻⁶ Ω·cm. -3 Ω·cm, with a change rate of approximately 4.17%.
[0050] Example 9 The amount of conductive particles used was 4.6 g, and the rest was the same as in Example 8. Resistivity was 3.5 × 10⁻⁶. -3 Ω·cm, 4.1×10 after aging -3 Ω·cm.
[0051] Example 10 The amount of conductive particles used was 5g, and the rest was the same as in Example 8. Resistivity was 2.1 × 10⁻⁶. -3 Ω·cm, 2.3×10 after aging -3 Ω·cm.
[0052] Comparative Example 1 In the electroless copper plating, 4g of DMAB was used (the rest was the same as in Example 1). Excessive reducing agent led to an excessively rapid homogeneous nucleation rate of copper ions in the solution, generating a large number of free copper particles. These free copper particles adhered to the microspheres, causing severe agglomeration. Monodisperse conductive particles could not be formed. The scanning electron microscope image is shown below. Figure 5 As shown in 'a'.
[0053] Comparative Example 2 The amount of CuSO4 used was 0.5 g. The copper ion concentration was too low, resulting in insufficient deposition driving force, sparse copper particle deposition on the microsphere surface, and poor conductivity (on-resistance > 20 Ω). The scanning electron microscope image is shown below. Figure 5 As shown in b in the figure.
[0054] Comparative Example 3 The amount of disodium EDTA used was 20.8 g. With excessive complexing agent, copper ions were over-complexed, resulting in an extremely low concentration of free copper ions, which could not effectively reduce the deposit. The scanning electron microscope image is shown below. Figure 5 As shown in c in the figure.
[0055] Comparative Example 4 The copper plating temperature was 30℃. If the reaction temperature is too low, the reduction reaction rate is slow, resulting in sparse copper particles on the microsphere surface. The scanning electron microscope image is shown below. Figure 5 As shown in d.
[0056] Comparative Example 5 Copper plating pH=11. The alkalinity is too strong; copper ions react with OH-. - The reaction produces Cu(OH)₂ precipitate, rendering the copper plating solution ineffective. Its scanning electron microscope image is shown below. Figure 5 As shown in e.
[0057] Comparative Example 6 No PANI or silver sulfate were added. No copper particles were deposited on the microsphere surface; copper ions freely nucleated in solution. This indicates that the microsphere surface lacks the ability to initiate chemical copper plating without active sites. The scanning electron microscope image is shown below. Figure 6 As shown in 'a'.
[0058] Comparative Example 7 Only PANI was added, without silver sulfate. Although PANI provided a certain number of reduction sites on the microsphere surface, the lack of a silver seed layer resulted in low reduction efficiency, uneven copper particle deposition, and severe agglomeration. The scanning electron microscope image is shown below. Figure 6 As shown in b in the figure.
[0059] Comparative Example 8 Silver sulfate was added without PANI. Silver ions could not be effectively adsorbed onto the surface of the unmodified microspheres, a silver seed layer could not be formed, and no copper deposition occurred on the microsphere surface. PANI adsorption and fixation of silver ions is a key step. The scanning electron microscope image is shown below. Figure 6 As shown in c in the figure.
[0060] Comparative Example 9 Without formate hydrothermal and thiol treatment, the amount of conductive particles used is 4g. Initial resistivity is 7.3 × 10⁻⁶. -3 Ω·cm. After aging at 85℃ / 85RH for 200h, the resistivity increases to over 200MΩ, indicating an insulating state.
[0061] Comparative Example 10 Without antioxidant treatment, the amount of conductive particles used is 4.6g. Initial resistivity is 3.1 × 10⁻⁶. -3 Ω·cm, insulation after aging.
[0062] Comparative Example 11 Without antioxidant treatment, the amount of conductive particles used is 5g. Initial resistivity is 1.9 × 10⁻⁶. -3 Ω·cm, insulation after aging.
[0063] The results of Comparative Examples 6 to 11 show that PANI modification and silver salt activation are two necessary conditions for achieving selective electroless copper plating on the surface of microspheres; the formate hydrothermal and thiol-treated antioxidant protective layer is the key to maintaining the conductivity of copper conductive particles in harsh environments for a long time.
[0064] In summary, the present invention provides a method for preparing antioxidant copper conductive particles, comprising: modifying the surface of polymer microspheres with conductive polymer materials to obtain polymer composite microspheres; The polymer composite microspheres were treated with a silver ammonia solution to obtain activated microspheres. These activated microspheres were then added to a copper plating solution containing copper salts, a complexing agent, and a reducing agent for electroless copper plating, yielding copper conductive particles. The copper conductive particles were then subjected to hydrothermal formate treatment and thiol treatment to form an antioxidant layer on the surface of the copper metal layer, resulting in antioxidant copper conductive particles. By using a combination of polyaniline and silver salts, the complex steps of roughening, sensitization, and activation in traditional electroless plating are replaced. The prepared copper conductive particles, after hydrothermal treatment with sodium formate and dodecyl mercaptan, exhibit excellent antioxidant properties. Using these core-shell structured particles as conductive fillers in conductive adhesives achieves cost savings, demonstrating superior value in terms of cost, and also exhibits high application stability, showing broad application prospects.
[0065] Finally, it should be noted that the above embodiments are only for illustrating the present invention and not for limiting the present invention. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art should understand that various combinations, modifications, or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention and should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing antioxidant copper conductive particles, characterized in that, Includes the following steps: By modifying the surface of polymer microspheres with conductive polymer materials, polymer composite microspheres are obtained. The polymer composite microspheres were treated with silver ammonia solution to obtain activated microspheres; The activated microspheres were added to a copper plating solution containing copper salt, complexing agent and reducing agent for chemical copper plating to obtain copper conductive particles; The copper conductive particles are subjected to formate hydrothermal treatment and thiol treatment in sequence to form an antioxidant layer on the surface of the copper conductive particles, thereby obtaining the antioxidant copper conductive particles.
2. The preparation method according to claim 1, characterized in that, The conductive polymer material is polyaniline and / or polydopamine.
3. The preparation method according to claim 1, characterized in that, The polymer microspheres are made of one or a copolymer of polystyrene, polymethyl methacrylate, polyurethane, phenolic resin, polydimethoxysiloxane, and silica. Preferably, the particle size of the polymer microspheres is 500 nm to 200 μm.
4. The preparation method according to claim 1, characterized in that, The silver ammonia solution is prepared by mixing silver salt and ammonia water, wherein the silver salt is silver sulfate or silver nitrate.
5. The preparation method according to claim 1, characterized in that, The copper salt is one or more of copper sulfate, copper chloride, and copper nitrate; the complexing agent is disodium ethylenediaminetetraacetate; and the reducing agent is one or more of dimethylamineborane, sodium hypophosphite, and sodium borohydride.
6. The preparation method according to claim 1, characterized in that, The temperature for the electroless copper plating is 30~70℃, and the pH is 7~9.
7. The preparation method according to claim 1, characterized in that, The formate is sodium formate or ammonium formate; the thiol is dodecyl mercaptan.
8. An antioxidant copper conductive particle prepared by the preparation method according to any one of claims 1 to 7, characterized in that, include: Polymer microspheres; A conductive polymer intermediate layer coating the surface of the polymer microspheres; A copper metal layer covering the surface of the conductive polymer intermediate layer; And an anti-oxidation layer formed on the surface of the copper metal layer.
9. A conductive adhesive, characterized in that, It comprises the antioxidant copper conductive particles, resin, and curing agent as described in claim 8.
10. The conductive adhesive according to claim 9, characterized in that, The resin includes thermosetting resins and / or thermoplastic resins, and the curing agent includes one or more of imidazole curing agents, acid anhydride curing agents, and amine curing agents.